Happiness in a Flux? The Instability Problem - Bykvist, K (2010)
In the recent discussion of happiness it has become popular to claim that being happy means having a certain positive attitude towards your life. This attitude involves both a judgement that your life measures up to your standards and a feeling of satisfaction with your life. In this paper, I am going to discuss a serious problem inherent in this account that has important ramifications for the normative question of how we ought to pursue happiness. If happiness is in part determined by your standards, how shall we determine whether you are happier in one life than in another when your standards change across these lives? Perhaps you will judge a life as a parent as better than a childless life, if you were to become a parent, but judge a childless life as better than a parenting life, if you were to remain childless. Which standard should determine the comparative happiness of the two lives? In this paper, I shall argue that some innocent-looking answers to this question will generate inconsistencies. To find an acceptable resolution, we need to make a difficult choice between what on the face of it look like two equally valid principles of happiness. © 2010 Springer Science+Business Media B.V.